Joint taxation in Spain and its effects on social welfare: A microsimulation analysis - Nuria Badenes Plá; Patricia Blanco Palmero; Borja Gambau-Suelves; María Navas Román; Noemí Villazán Pellejero (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper focuses on the study of the effects on social welfare generated by the scheme of joint taxation of the Spanish Personal Income Tax (PIT), whose peculiarity linked to its condition of optionality, allows the minimization of households' tax bill. Different scenarios are simulated using the tax-benefit microsimulator of the European Commission - EUROMOD - with data from the Survey on Income and Living Conditions corresponding to 2016. In order to measure the welfare, the current PIT scheme is taken as reference and then it is compared with two alternatives, one, in which the families that currently can opt for this system are forced to pay jointly, and another, in which the only taxation scheme was individual. The results show that the Spanish system is revealed as a generator of additional welfare linked both to the circumstance of allowing an option to families, as well as to the fact of designing a specific system of joint taxation. In addition, it is shown that the policy recommendations would be different if only the study of inequality had been considered, since the net income gains of the current system offset the possible improvements in inequality of the simulated alternatives. Our results, therefore, also reinforce the convenience of adopting an approach that simultaneously considers efficiency and equity.
Keywords: C65; D63; H21; H31; 330; microsimulation; EUROMOD; social welfare; inequality; family taxation